ENGINEERING INSURANCE (Program Studi Magister Manajemen Lingkungan, 2019)
Engineering insurance is one of the most general and effective methods of project risk management in Western countries with a perfect insurance system. It covers damage to plant, machinery, and other engineering equipment such as boilers, computers, cranes, and lifts. Professional liability insurance, a type of engineering insurance, covers errors and omissions in the services provided by businesses. General liability insurance helps cover bodily injury claims, property damage, and reputational harm, among other risks. Engineering project insurance strategy simulation models can be used to analyze and optimize insurance strategies for projects. Cash flow modeling is an important aspect of insurance business, and efficient methodologies have been proposed to address this.